Drosophila Lipase 3 Mediates the Metabolic Response to Starvation and Aging - Hänschke, Lea; Heier, Christoph; Maya Palacios, Santiago José; Özek, Huseyin Erdem; Thiele, Christoph; Bauer, Reinhard; Kühnlein, Ronald P.; Bülow, Margret H. (Frontiers in Aging, 2022)
The human LIPA gene encodes for the enzyme lysosomal acid lipase, which hydrolyzes cholesteryl ester and triacylglycerol. Lysosomal acid lipase deficiency results in Wolman disease and cholesteryl ester storage disease. The Drosophila genome encodes for two LIPA orthologs, Magro and Lipase 3. Magro is a gut lipase that hydrolyzes triacylglycerides, while Lipase 3 lacks characterization based on mutant phenotypes. We found previously that Lipase 3 transcription is highly induced in mutants with defects in peroxisome biogenesis, but the conditions that allow a similar induction in wildtypic flies are not known. Here we show that Lipase 3 is drastically upregulated in starved larvae and starved female flies, as well as in aged male flies. We generated a lipase 3 mutant that shows sex-specific starvation resistance and a trend to lifespan extension. Using lipidomics, we demonstrate that Lipase 3 mutants accumulate phosphatidylinositol, but neither triacylglycerol nor diacylglycerol. Our study suggests that, in contrast to its mammalian homolog LIPA, Lipase 3 is a putative phospholipase that is upregulated under extreme conditions like prolonged nutrient deprivation and aging.